Diffusion tensor imaging of the nigrostriatal fibers in Parkinson's disease. Issue 9 (29th April 2015) - Zhang, Yu; Wu, I‐Wei; Buckley, Shannon; Coffey, Christopher S.; Foster, Eric; Mendick, Susan; Seibyl, John; Schuff, Norbert
Abstract Background Parkinson's disease (PD) is histopathologically characterized by the loss of dopamine neurons in the substantia nigra pars compacta. The depletion of these neurons is thought to reduce the dopaminergic function of the nigrostriatal pathway, as well as the neural fibers that link the substantia nigra to the striatum (putamen and caudate), causing a dysregulation in striatal activity that ultimately leads to lack of movement control. Based on diffusion tensor imaging, visualizing this pathway and measuring alterations of the fiber integrity remain challenging. The objectives were to 1) develop a diffusion tensor tractography protocol for reliably tracking the nigrostriatal fibers on multicenter data; 2) test whether the integrities measured by diffusion tensor imaging of the nigrostriatal fibers are abnormal in PD; and 3) test whether abnormal integrities of the nigrostriatal fibers in PD patients are associated with the severity of motor disability and putaminal dopamine binding ratios. Methods Diffusion tensor tractography was performed on 50 drug‐naïve PD patients and 27 healthy control subjects from the international multicenter Parkinson's Progression Marker Initiative. Results Tractography consistently detected the nigrostriatal fibers, yielding reliable diffusion measures. Fractional anisotropy, along with radial and axial diffusivity of the nigrostriatal tract, showed systematic abnormalities in patients. In addition, variations in fractional anisotropy and radial diffusivity of the nigrostriatal tract were associated with the degree of motor deficits in PD patients. Conclusion Taken together, the findings imply that the diffusion tensor imaging characteristic of the nigrostriatal tract is potentially an index for detecting and staging of early PD. © 2015 International Parkinson and Movement Disorder Society